Design study of the SSC-LINAC re-buncher - 杨柳 鲁向阳 全胜文 姚中元 罗星 周奎 孙列鹏 赵红卫 孙周平 何源 石爱民 肖陈 杜小楠 张聪 张周礼 (Chinese physics C, 2013)
A re-buncher with spiral arms for a heavy ion linear accelerator named as SSC-LINAC at HIRFL （the heavy ion research facility of Lanzhou） has been constructed. The re-buncher, which is used for beam longitudinal modulation and matching between the RFQ and DTL, is designed to be operated in continuous wave （CW） mode at the Medium-Energy Beam-Transport （MEBT） line to maintain the beam intensity and quality. Because of the longitudinal space limitation, the re-buncher has to be very compact and will be built with four gaps. We determined the key parameters of the re-buncher cavity from the simulations using Microwave Studio software, such as the resonant frequency, the quality factor Q and the shunt impedance. The detailed design of a 53.667 MHz spiral cavity and measurement results of its prototype will be presented.